2016
DOI: 10.1021/jacs.6b05695
|View full text |Cite
|
Sign up to set email alerts
|

New Mechanism for Photocatalytic Reduction of CO2 on the Anatase TiO2(101) Surface: The Essential Role of Oxygen Vacancy

Abstract: Photocatalytic reduction of CO into organic molecules is a very complicated and important reaction. Two possible pathways, the fast-hydrogenation (FH) path and the fast-deoxygenation (FdO) path, have been proposed on the most popular photocatalyst TiO. We have carried out first-principles calculations to investigate both pathways on the perfect and defective anatase TiO(101) surfaces to provide comprehensive understanding of the reaction mechanism. For the FH path, it is found that oxygen vacancy on defective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
208
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(223 citation statements)
references
References 57 publications
11
208
0
4
Order By: Relevance
“…F, Schematic illustration of electron-hole separation in facet engineered reduced TiO 2 . Reproduced with permission from Reference, 66 Copyright 2017, The Royal Society of Chemistry Energetic study of photocatalytic CO 2 reduction on defective TiO 2 was reported by Ji et al 67 They found that oxygen vacancy at the anatase TiO 2 (101) surface has much higher activity on CO 2 reduction than Ti atom in the perfect surface. Also, Liu et al 68 found that oxygen vacancy can either improve the binding of CO 2 , activation, and dissociation or stabilize the reaction intermediates.…”
Section: Applications In Photocatalytic Co 2 Reductionmentioning
confidence: 99%
“…F, Schematic illustration of electron-hole separation in facet engineered reduced TiO 2 . Reproduced with permission from Reference, 66 Copyright 2017, The Royal Society of Chemistry Energetic study of photocatalytic CO 2 reduction on defective TiO 2 was reported by Ji et al 67 They found that oxygen vacancy at the anatase TiO 2 (101) surface has much higher activity on CO 2 reduction than Ti atom in the perfect surface. Also, Liu et al 68 found that oxygen vacancy can either improve the binding of CO 2 , activation, and dissociation or stabilize the reaction intermediates.…”
Section: Applications In Photocatalytic Co 2 Reductionmentioning
confidence: 99%
“…The intermediate reactants can be various and the pathway of redox reaction can be influenced by the surface chemical environment of photocatalysts and the reaction environment. [36][37][38][39][40][41][42][43][44][45][46] www.advancedsciencenews.com Although a number of reviews have been published that summarize the effectiveness of these strategies, [2,[6][7][8]22,23] virtually none have reviewed the literature from the perspective of the impact of atomic-level reactive sites. This is important as these influence the adsorption and activation of CO 2 molecules and intermediate products thereby leading to different activity and selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…The development of photocatalysts with high activity, selectivity, and durability to improve the efficiency of CO 2 conversion has been a prominent quest to overcome these limitations. In this regard, various approaches have been devised to provide more surface‐active sites, enhance electron–hole pair generation and separation, and reduce the kinetic barrier of the reactivity …”
Section: Introductionmentioning
confidence: 99%
“…In thisr egard, various approaches have been devised to provide more surface-active sites, enhancee lectron-hole pair generation and separation, and reduce the kinetic barrier of the reactivity. [5][6][7][8] Very recently,d efecte ngineering has been recognized to be ak ey factor affecting the adsorption and activation ability of photocatalysts. The presence of appropriate vacancies can alter the electronic structure, improve the surface adsorption, and create more active sites, resultingi ne xcellent photocatalytic properties.…”
Section: Introductionmentioning
confidence: 99%